2015
DOI: 10.1111/age.12343
|View full text |Cite
|
Sign up to set email alerts
|

Identification and profiling of microRNAs associated with white and black plumage pigmentation in the white and black feather bulbs of ducks by RNA sequencing

Abstract: MicroRNAs (miRNAs) play important roles in many biological processes by regulating gene expression at the post-transcriptional level. However, the mechanism by which specific miRNAs may regulate plumage pigmentation has remained largely elusive. In this study, we sequenced miRNAs using Solexa sequencing and then performed a detailed analysis of their expression profiles between the black and white feather bulbs of ducks from Cui Hei, Kaiya, Liancheng pure breeds and a Kaiya-Liancheng F2 population. mirdeep2 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…These include gga-miR-204, which is a miRNA known to be associated with melanogenesis. The expression of gga-miR-204 is significantly different between black and white feather bulbs in ducks (Apopo et al 2015), and is also associated with skin colour in fish (Yan et al 2013). In our study, gga-miR-204 was up-regulated in chickens with black skin, similar to results from previous studies (Adijanto et al 2012b;Apopo et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These include gga-miR-204, which is a miRNA known to be associated with melanogenesis. The expression of gga-miR-204 is significantly different between black and white feather bulbs in ducks (Apopo et al 2015), and is also associated with skin colour in fish (Yan et al 2013). In our study, gga-miR-204 was up-regulated in chickens with black skin, similar to results from previous studies (Adijanto et al 2012b;Apopo et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has indicated that miRNAs can target genes or pathways involved in melanocyte biology (Mione and Bosserhoff 2015). In other vertebrates, such as ducks (Apopo et al 2015), alpacas (Xue et al 2012), goats (Wu et al 2014), mice (Dynoodt et al 2013), and fish (Yan et al 2013), miRNAs are known to be responsible for pigmentation. However, no studies to date have reported on the role of miRNAs in determining skin colour in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 To date, studies have shown a close connection between miRNA, UVB irradiation, 33 and skin. [15][16][17] Although several studies have examined functional roles for miRNAs in the regulation of pigmentation of different species, [34][35][36] to our knowledge, such a role for miRNAs in the regulation of genes critical to pigmentation has not been demonstrated in normal adult melanocytes. Moreover, in melanoma cells, miR-340 can bind to the 3 0 -UTR of MITF mRNA and mediate the degradation of its mRNA, reducing the expression and activity of MITF protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to DNA sequencing, it is possible to analyze genetic variability of production traits and phenotypic characteristics of animals. Analysis at the molecular level will facilitate selection of the animals resistant to pathogens or carrying favorable production traits (3).…”
Section: Application Of Next Generation Sequencingmentioning
confidence: 99%